Conjunction of triboelectric nanogenerator with induction coils as wireless power sources and self-powered wireless sensors - Zhang, Chi (Nat Commun, 2020)
Here we demonstrate a magnetic resonance coupling based wireless triboelectric nanogenerator (TENG) and fully self-powered wireless sensors. By integrating a microswitch and an inductor with the TENG, the pulsed voltage output is converted into a sinusoidal voltage signal with a fixed frequency. This can be transmitted wirelessly from the transmit coil to the resonant-coupled receiver coil with an efficiency of 73% for a 5 cm distance between the two coils (10 cm diameter). Analytic models of the oscillating and coupled voltage signals for the wireless energy transfer are developed, showing excellent agreement with the experimental results. A TENG of 40 × 50 mm(2) can wirelessly light up 70 LEDs or charge up a 15 μF capacitor to 12.5 V in ~90 s. The system is further utilized for two types of fully self-powered wireless chipless sensors with no microelectronic components. The technologies demonstrate an innovative strategy for a wireless ‘green’ power source and sensing.